2013
DOI: 10.1111/1469-0691.12149
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and sensitive diagnosis of Acanthamoeba keratitis by loop-mediated isothermal amplification

Abstract: A loop-mediated isothermal amplification (LAMP) assay was developed for the detection of Acanthamoeba. The sensitivity of the LAMP assay was tested using different copies of positive DNA. The specificity of the assay was tested using DNA extracted from Acanthamoeba, Pseudomonas aeruginosa, Candida albicans, herpes simplex virus-1 and human corneal epithelial cells. Its effectiveness was evaluated and compared with culture, corneal smear examination and real-time PCR in corneal samples from mice with Acanthamoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…LAMP has been widely used as a tool in disease diagnosis (12,13), detection of food-borne Pathogenic microorganisms (14) and rapid authentication of ingredients (15). In the present study, the LAMP method developed was specific for ETEC strain and had no amplified product for 9 non-E.coli strains.…”
Section: Discussionmentioning
confidence: 80%
“…LAMP has been widely used as a tool in disease diagnosis (12,13), detection of food-borne Pathogenic microorganisms (14) and rapid authentication of ingredients (15). In the present study, the LAMP method developed was specific for ETEC strain and had no amplified product for 9 non-E.coli strains.…”
Section: Discussionmentioning
confidence: 80%
“…Group 2L-3d showed the highest clinical scores of epithelial defect, corneal edema, neovascularization, and opacity/infiltration, with the only two cases of keratomalacia (lower right corner) and endophthalmitis noted. 4,5,9,10,12,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] In the majority of them, the cornea was partially or completely abraded with a sterile cotton applicator, scratched with a syringe needle or scraped with a blade before placing the contact lens, 4,5,9,10,16-30 because van Klink et al 12 and Ledbetter et al demonstrated that this lesion was essential to allow the penetration of Acanthamoeba into the cornea (Ledbetter EC, et al IOVS 2012;53:ARVO E-Abstract 6146). In this study, the epithelial debridement was performed with a diamond burr unit, used for removing the nonadherent epithelial tissue in the management of spontaneous chronic corneal epithelial defects in dogs and horses.…”
Section: Discussionmentioning
confidence: 99%
“…19,23,24,[26][27][28]30 However, good results have been shown using exposure times of 24 hours in rats and mice, 4 to 5 days in pigs and 3 to 6 days in hamsters, but not with 4 to 5 days in rabbits. 4,5,9,10,[16][17][18][20][21][22]25,29 Contact lenses serve as a mechanical vector for transmitting trophozoites to the corneal surface, facilitating parasite binding to the epithelium. The adhesion is regulated mainly by mannosylated glycoproteins, and the use of contact lenses and presence of a previous abrasion or mild trauma have been correlated with an increased expression of these proteins on the epithelium, promoting the adhesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though detection limits for diagnostic methods are usually determined using pure pathogen DNA, 183,184 in a real world situation DNA extracted from an infected plant contains a complex mixture of genomic DNA from the plant as well as the pathogen. The ratio of plant DNA to pathogen DNA in a given sample is variable as it depends on the pathogen and disease progression, but even in advanced stages of infection, plant DNA will always be present in vast excess over pathogen DNA.…”
Section: Sensitivity Analysismentioning
confidence: 99%